Pricing basket weather derivatives on rainfall and temperature processes - Nelson Christopher Dzupire; Philip Ngare; Leo Odongo (International Journal of Financial Studies, 2019)
This paper follows an incomplete market pricing approach to analyze the evaluation of weather derivatives and the viability of a weather derivatives market in terms of hedging. A utility indifference method is developed for the specification of indifference prices for the seller and buyer of a basket of weather derivatives written on rainfall and temperature. The agent's risk preference is described by an exponential utility function and the prices are derived by dynamic programming principles and corresponding Hamilton Jacobi-Bellman equations from the stochastic optimal control problems. It is found the indifference measure is equal to the physical measure as there is no correlation between the capital market and weather. The fair price of the derivative should be greater than the seller's indifference price and less than the buyer's indifference price for market viability and no arbitrage opportunities.
Keywords: 330; incomplete market; basket option; indifference price; utility function; dynamic programming principle; Hamilton Jacobi-Bellman equations